School autonomy reform in Queensland: governance, freedom and the entrepreneurial leader - Keddie, A.; Gobby, Brad; Wilkins, C. (Carfax, 2017)
This paper examines conceptions of governance and freedom embedded within a new school autonomy policy in Queensland (Australia). Drawing on interview data from case study research, it foregrounds the practices of two school leaders from a secondary school in regional Queensland. It considers how such conceptions foster an entrepreneurial leadership of competition and compliance but also how they create space for something other than these dominant performative priorities. The paper’s theoretical contribution responds to calls for more nuanced accounts of entrepreneurial leadership to better understand how current performative demands are impacting on school leaders amid increasingly autonomised education systems.